Formation of stable DNA triplexes. - Fox, K; Brown, T (2011)
Triple-helical nucleic acids are formed by binding an oligonucleotide within the major groove of duplex DNA. These complexes offer the possibility of designing oligonucleotides which bind to duplex DNA with considerable sequence specificity. However, triple-helix formation with natural nucleotides is limited by (i) the requirement for low pH, (ii) the requirement for homopurine target sequences, and (iii) their relatively low affinity. We have prepared modified oligonucleotides to overcome these limitations, including the addition of positive charges to the sugar and/or base, the inclusion of cytosine analogues, the development of nucleosides for recognition of pyrimidine interruptions and the attachment of one or more cross-linking groups. By these means we are able to generate triplexes which have high affinities at physiological pH at sequences that contain pyrimidine interruptions.